(untitled) (Research, Society and Development, 2021)
Rheedia acuminata is a fruit species native to the Amazon with potential for fresh consumption. The objective of this work was to study the production of seedlings with the addition of organic matter using different concentrations of poultry litter to the substrate. The experiment was carried out in the seedling production nursery of the Fruit Laboratory of Embrapa Amazônia Oriental, Belém, Pará, Brazil. A completely randomized design was adopted, the treatments consisted of the following mixtures of soil with aviary bedding (0%, 10%, 20%, 30% and 40%), with four repetitions of ten seedlings per plot. To characterize the seedling growth, the following evaluations were performed: height, stem diameter, number of leaves, shoot dry mass, root dry mass, total dry mass and Dickson quality index. Morphological parameters and Dickson quality index observed in seedlings were affected by substrate composition. It is concluded that for the production of Rheedia acuminata seedlings, vigorous and capable of being taken to the field, 20% to 30% of aviary bedding should be added to the soil for the composition of the substrate.